Building Public Involvement: Increasing Public Awareness Of The Importance Of Quality Of Education - Hasan Baharun; Shofa Aulia Kumala; Nadya Nadya (At-Tarbiyat, 2024)
This article aims to analyze several effective strategies used by SD Insan Terpadu to build public awareness of the quality of children's education. This research method is a descriptive qualitative method with a case study approach. Data collection techniques were carried out using interviews, observation and documentation. Sources were selected using a purposive sampling method. Data analysis uses the Milles and Huberman concept which consists of three activities, namely data presentation, data reduction, as well as drawing conclusions and data verification. The research results show that the strategies used by SD Insan Terpadu to build public awareness of the quality of children's education include: (1) active communication with parents, (2) parent participation in parenting seminars, (3) collaboration with the local community, and (4) ) use of social media. By implementing this strategy, SD Insan Terpadu strives to create an educational environment that supports children's overall development by involving and building support from the community.